'The Choicest, Best-Arranged Museums I Have Ever Seen': The Pitt-Rivers Museum, Farnham, Dorset, 1880s–1970s. Issue 2 (July 2014) - Saunders, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> The privately owned Pitt-Rivers Museum in Farnham, Dorset, was established by General Pitt-Rivers in the early 1880s. A discussion of the original purpose of the museum and its early development is followed by an account of its later history.